Exploration of anti-stress mechanisms in high temperature exposed juvenile golden cuttlefish (Sepia esculenta) based on transcriptome profiling - Wang, Yongjie; Bao, Xiaokai; Wang, Weijun; Xu, Xiaohui; Liu, Xiumei; Li, Zan; Yang, Jianmin; Yuan, Tingzhu (Frontiers in Physiology, 2023)
Sepia esculenta is a cephalopod widely distributed in the Western Pacific Ocean, and there has been growing research interest due to its high economic and nutritional value. The limited anti-stress capacity of larvae renders challenges for their adaptation to high ambient temperatures. Exposure to high temperatures produces intense stress responses, thereby affecting survival, metabolism, immunity, and other life activities. Notably, the molecular mechanisms by which larval cuttlefish cope with high temperatures are not well understood. As such, in the present study, transcriptome sequencing of S. esculenta larvae was performed and 1,927 differentially expressed genes (DEGs) were identified. DEGs were subjected to functional enrichment analyses using the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases. The top 20 terms of biological processes in GO and 20 high-temperature stress-related pathways in KEGG functional enrichment analysis were identified. A protein-protein interaction network was constructed to investigate the interaction between temperature stress-related genes. A total of 30 key genes with a high degree of participation in KEGG signaling pathways or protein-protein interactions were identified and subsequently validated using quantitative RT-PCR. Through a comprehensive analysis of the protein-protein interaction network and KEGG signaling pathway, the functions of three hub genes (HSP90AA1, PSMD6, and PSMA5), which belong to the heat shock protein family and proteasome, were explored. The present results can facilitate further understanding of the mechanism of high temperature resistance in invertebrates and provide a reference for the S. esculenta industry in the context of global warming.